Mouse model of SARS-CoV-2 reveals inflammatory role of type I interferon signaling - Israelow, Benjamin (bioRxiv, 2020)
Severe Acute Respiratory Syndrome- Coronavirus 2 (SARS-Cov-2) has caused over 5,000,000 cases of Coronavirus disease (COVID-19) with significant fatality rate.(1–3) Due to the urgency of this global pandemic, numerous therapeutic and vaccine trials have begun without customary safety and efficacy studies.(4) Laboratory mice have been the stalwart of these types of studies; however, they do not support infection by SARS-CoV-2 due to the inability of its spike (S) protein to engage the mouse ortholog of its human entry receptor angiotensin-converting enzyme 2 (hACE2). While hACE2 transgenic mice support infection and pathogenesis,(5) these mice are currently limited in availability and are restricted to a single genetic background. Here we report the development of a mouse model of SARS-CoV-2 based on adeno associated virus (AAV)-mediated expression of hACE2. These mice support viral replication and antibody production and exhibit pathologic findings found in COVID-19 patients as well as non-human primate models. Moreover, we show that type I interferons are unable to control SARS-CoV2 replication and drive pathologic responses. Thus, the hACE2-AAV mouse model enables rapid deployment for in-depth analysis following robust SARS-CoV-2 infection with authentic patient-derived virus in mice of diverse genetic backgrounds. This represents a much-needed platform for rapidly testing prophylactic and therapeutic strategies to combat COVID-19.